SHORT COMMUNICATION: POTENSI TANAMAN HERBAL UNTUK IMUNITAS IKAN TERHADAP PAPARAN BAKTERI Aeromonas sp - ANDRI ANDRI (Akuatik: Jurnal Sumberdaya Perairan, 2013)
One of the causes of disease in fish is declining immunity or immunity. Giving an immunostimulatory treatments deemed effective enough to reduce some of the infections that occur in addition to the use of drugs. Studies related to the use of immunostimulants in fish immune enhancement has a lot to do, both in the form of synthetic chemicals, microorganisms intact and component derivatives, as well as natural immunostimulatory ingredients derived from animal and plant groups and derivatives. Short communication study aims to elaborate immunostimulant, especially the potential of herbal plants that have been implemented so far to improve the immunity of fish infected by Aeromonas sp in freshwater fish commodities